Aflatoxins and Aflatoxigenic Fungi Contamination of Dried Fruits in Iraqi Market - Mohammad J. Al-Jassani (Journal of Global Pharma Technology, 2017)
Objectives: Studying the incidence of Aspergillus sp. and Aflatoxins (AFs) contamination in dried fruits collected from local market of Hilla city and other origins. Methods: Intergenic fungi were isolated by direct plate method and were morphologically identified on specified media. AFs production by Aspergillus spp. were screened and determined by thin layer chromatography (TLC) and high performance liquid chromatography (HPLC). Results: Aspergillus spp. represented 93.33% of the total isolated mold species. A. niger was dominant (79.61%) and A. flavus was only 12.5%. Of the total Aspergillus spp., 54.4% found active aflatoxin B1 (AFB1) and aflatoxin B2 (AFB2) producers among 85.24% belong to A. niger and 14.75% belong to A. flavus. HPLC shows that 100% of dried fruit samples tested positive for AFs. Conclusion: Through our study the mold isolates showed different AFs production behavior that they are able to produce AFB1 and AFB2 at a pH range (3.1 to 4.5), optimum temperature at range (28-32ºC) and low aw for best AFs production and this needs much concern especially with dried fruit storage and treatment conditions.Keywords: Dried fruit, Aflatoxin, Aflatoxigenic fungi, TLC, HPLC.